2020
DOI: 10.2478/amns.2020.2.00022
|View full text |Cite
|
Sign up to set email alerts
|

Periodic orbit in the frame work of restricted three bodies under the asteroids belt effect

Abstract: In this paper, we present a comprehensive analytical study on the perturbed restricted three bodies problem. We formulate the equations of motion of this problem, in the event of the asteroids belt perturbation. We find the locations of equilibrium points (collinear and triangular points) and analysis their linear stability. Furthermore the periodic orbits around both collinear and triangular points are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…erefore, this paper improves the accuracy of rumor discovery on the premise of ensuring the timeliness of rumor discovery. With the development of science and technology, there is an increasing trend about the investigation of the real world problems such as the development of Faults Detection [25], Vortex eory [26], Periodic Orbit [27], Dynamics [28] and other research fields. It is hoped that the model proposed in this paper can be applied to these problems in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, this paper improves the accuracy of rumor discovery on the premise of ensuring the timeliness of rumor discovery. With the development of science and technology, there is an increasing trend about the investigation of the real world problems such as the development of Faults Detection [25], Vortex eory [26], Periodic Orbit [27], Dynamics [28] and other research fields. It is hoped that the model proposed in this paper can be applied to these problems in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen from the simulation results, on the premise that other parameters remain unchanged: (1) With the increase of core spacing, the signal tance between the core and the shaft. And the sensitivity of the foreslope gradually decreases [9,10]. From this analysis, it is concluded that the distance between the fibre core axis of the optical fibre probe should be as small as possible, that is, the sending fibre and the receiving fibre should be closely arranged within the range of conditions.…”
Section: Intensity Modulation Model Of Fibre Bundle Sensormentioning
confidence: 91%
“…On the premise of fully considering the geological environment near the tunnel and minimising the so-called 'boundary effect', the distance between the boundary of the calculation model and the centreline of the tunnel is 45 m, and the distance from the bottom boundary to the top of the tunnel is 30 m. Surface. According to the characteristics of the bias tunnel, the upper boundary is the free boundary, the left and right boundaries are horizontal constraints and the upper boundary is the vertical displacement constraint [9,10]. There are 1876 quadrilateral elements and the total number of nodes is 1847.…”
Section: Calculation Modelmentioning
confidence: 99%